Mapping land surface temperature in Nigeria using Modis data - M. Menegbo, Emmanuel (International Journal of Advanced Geosciences, 2024)
In developing countries such as Nigeria, rapid land degradation is an unavoidable phenomenon. Nigeria is experiencing significant growth as its population clusters continue to expand due to migration from rural areas. Unfortunately, one of the negative consequences of this de-velopment is the increase in impervious areas, which results in higher land surface temperatures (LST). A number of studies have highlight-ed the utilization of Landsat thermal data and the usefulness of MODIS data in the preparation of LST maps. This current study aimed to produce LST maps for Nigeria using 8-day average MODIS MOD11A2 images for the years 2001, 2011, and 2015, allowing for an as-sessment of the average LST for the country. Analysis of the LST maps reveals that the average temperature in Nigeria is 32°C, with the highest and lowest LSTs recorded as 43°C and 20°C respectively within the selected years. These results indicate that impervious areas contain a greater number of pixels falling into the high to very high-class category. It is crucial to adopt appropriate climate change mitiga-tion measures in light of these findings.